Influence of allelopatic mulch on weed growth and postharvest quality of leaf lettuce (Lactuca sativa L.) - Ketaren, Bunga Raya (2013)
Today, there is a high demand for our food supply to be free of potentially toxic substances including those used in the production of raw products. During the production and processing of agricultural commodities, various chemicals and foreign substances such as pesticide may enter food commodities. Most pesticides are acutely toxic and can produce adverse health effects in humans and animals when ingested at low levels over long periods of time. A study was conducted to identify allelopathic mulch for sustainable weed control of leaf lettuce and determine its effect on postharvest quality characteristics. A quantitative survey was done to investigate major weeds selected leafy vegetable fields in Selangor. Ten weed species were recorded. Cyperus rotundus and Ageratum conyzoides were the most abundant weeds followed by Eleuthranthera ruderalis, Amaranthus spinosus, and Cyperus kyllingia. Selecting allelopathic mulch to inhibit weed seeds germination was studied using extracts of sorghum, paddy straw and empty oil palm fruit bunch (EFB) in a growth chamber. Total germinated seeds were recorded every 24 hour. Shoot and root lengths were measured on germination day 20. Allelopathy residues were detrimental to germination percentage, germination speed,mean germination time and relative hypocotyl and root length of weed species studied. Cucumber, cabbage and sunflower allelochemicals inhibited 100% germination of C. rotundus, A. conyzoides, E. ruderalis, A. spinosus and C. kyllingia. Sorghum, paddy straw and EFB caused 30-50% germination for C. kyllingia, Seed germination of C. rotundus, A. conyzoides, E. ruderalis and A. spinosus was 10-30% when treated with extract sorghum, paddy straw and EFB. Germination of E. ruderalis was lowest when treated with EFB than other weeds. Final seed germination and seedling growth was reduced 0-50% with sorghum,paddy straw and EFB mulch residues. Effectiveness of sunflower and cucumber mulch on leaf lettuce was studied on vegetable field plot. Types and rates of mulching did not affect soils moisture content and total N, P, K, Mg and Ca. Higher total phenolic content and phenolic soluble concentration occurred in soils with cucumber mulch residue compared to control. Seventeen weed species belonging to six families was observed in Leaf lettuce crop. Unmulched plot had 14 weed species of family Poaceae, three Cyperaceae, two each of Euphorbiaceae and Asteraceae and one each of Amaranthaceae and Portulacaceae. Sum dominance ratio showed five most dominant weed encountered were C. rotundus, C. distans, A. spinosus, C. kyllingia and A. conyzoides. Sunflower (5 ton/ha) and cucumber (15 ton/ha) mulched plots caused reduction to five weed species. Highest reduction was for A. spinosus. Sum dominance ratio of weeds with sunflower mulch residues (10 and 15 ton/ha) was high for C. rotundus, and similar to 10 ton/ha cucumber mulch. Cucumber mulch at 5 ton/ha successfully suppressed C. rotundus in leaf lettuce plots. Mulching did not affect postharvest quality of Leaf lettuce. All characteristics measured (firmness, pH, TA and AA) were not different from unmulched treatment. Mulch rates did not affect quality characteristics and soil nutrients of leaf lettuce. Cucumber and sunflower mulching controlled weeds effectively and has potential as alternative chemical herbicides. Studies should be conducted for longer period for optimum mulch residues effectiveness.